2023
DOI: 10.1519/jsc.0000000000004477
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Pitch Counts and Shoulder Strength in Collegiate Baseball Players

Abstract: Relationship between pitch counts and shoulder strength in collegiate baseball players. J Strength Cond Res 37(9): 1860-1864, 2023-Large volumes of throwing leads to changes in shoulder strength that have been associated with increased risk of injury. The purpose of this study was to investigate the relationship between throwing volume and eccentric shoulder strength. Twelve NCAA Division I baseball pitchers volunteered to participate. Prepractice and postpractice eccentric shoulder strength was measured using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…Further research has detailed the changes in shoulder muscle strength profiles after acute bouts of single session throwing in collegiate level pitchers. Gagnon et al 22 found no changes in external and internal rotation strength while Mirabito et al 23 found a reduction in external rotation strength. Mullaney et al 19 found minimal changes in scapular stabilizer strength and a gross reduction in shoulder strength with the exception of external rotation and strength in the empty can testing position.…”
Section: Introductionmentioning
confidence: 98%
“…Further research has detailed the changes in shoulder muscle strength profiles after acute bouts of single session throwing in collegiate level pitchers. Gagnon et al 22 found no changes in external and internal rotation strength while Mirabito et al 23 found a reduction in external rotation strength. Mullaney et al 19 found minimal changes in scapular stabilizer strength and a gross reduction in shoulder strength with the exception of external rotation and strength in the empty can testing position.…”
Section: Introductionmentioning
confidence: 98%